Physical activity during summer and recognition of heatstroke prevention among patients with cardiovascular disease in an urban area of Japan: a descriptive study - Takuji Adachi; Yuki Tsunekawa; Daisuke Tanimura (BMC Research Notes)
Abstract Objective Patients with cardiovascular disease are considered a high-risk population for heat-related illnesses. This study aimed to describe the difference in physical activity between summer and fall among patients with cardiovascular disease and their recognition of heatstroke prevention in an urban area with high temperature conditions. Results We enrolled 56 outpatients who participated in cardiac rehabilitation in the summer of 2022 (median age, 75 years [interquartile range, 68–80]). Physical activity level for each patient was assessed using the International Physical Activity Questionnaire at baseline in summer (August) and follow-up in fall (October). Changes in exercise habits and frequency of going outside during the study period and the patients’ recognition of heatstroke prevention were assessed using questionnaires. The prevalence of low physical activity was higher in summer than in fall (57.1% vs. 37.5%, p = 0.013). Of the patients involved in self-exercise before summer, 33.9% answered that their exercise habits decreased in summer. Of them, 47.4% felt that their exercise habits remained decreased in fall. Regarding the frequency of going outside, 82.1% went outside less in summer. Most participants were highly interested in heatstroke prevention.